The unique challenges of AYA cancer care in resource-limited settings - Hovsepyan, Shushan; Hoveyan, Julieta; Sargsyan, Lilit; Hakobyan, Lusine; Krmoyan, Lusine; Kamalyan, Alisa; Manukyan, Narek; Atoyan, Stepan; Muradyan, Armen; Danelyan, Samvel; Tamamyan, Gevorg; Bardakhchyan, Samvel; et al. (Frontiers in Adolescent Medicine, 2023)
Introduction Adolescents and young adults (AYAs) diagnosed with cancer represent a distinct group with exceptional and unique characteristics. The survival rates for this age group are worse than in children or adults. Cancer care for this population is a challenge, not only for low-income countries but also for the developed world. This review addresses the unique challenges adolescents and young adults (AYAs) diagnosed with cancer in low-income countries face. Methods Two individual authors conducted the literature review to present the global burden of AYAs in resource-limited settings. The articles selected focused on AYA care from Latin America, Asia, and Africa. Results Among the challenges of managing AYAs with cancer are the absence of national and/or hospital cancer registries, and a lack of adequate infrastructure, AYA-dedicated programs, appropriate psycho-social support, fertility preservation, and genetic counseling services. Furthermore, education and training activities specifically dedicated to the care of AYAs diagnosed with cancer are scarce in those countries. Conclusion Implementing a dedicated AYA program in resource-limited settings will be critical in providing patient-centered care bolstered by age-appropriate infrastructure and comprehensive clinical, psycho-social, and allied health support. It will significantly reduce the treatment abandonment rate, diminish the duration of diagnosis delay, and alleviate emotional detachment and disarray.